The many deaths of barnaby james (2023) ebook - Gibson, Neil (The Many Deaths of Barnaby James., 2023)
Every year, the circus comes to town.However, ""The Black Top"" isn't like any you've seen before—its performers were once dead and they've been resurrected by their fearsome ringmaster, AZLON.BARNABY JAMES, a young gravedigger, requests that Azlon resurrect the love of his (former) life, DELILAH. Time and time again, his pleas are rejected. Frustrated, Barnaby decides to steal Azlon's magic wand and bring back Delilah himself. On his desperate journey to find her, Barnaby must overcome murderers, cannibals, and sex slavers, not to mention the full fury of Azlon, or he might just find himself dead…again.